Institutional reform of international environmental policy: advancing the debate on a world environment organization - Frank Biermann; Udo E. Simonis (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
With the onset of the new millennium, the longstanding need for reform of the United Nations system has gained new momentum. Efficiency gains and better coordination are desirable, though not sufficient to bring about improvement in international relations. It could therefore make sense to look for institutional innovations that would upgrade the pressing tasks of environmental and development policy in the eyes of national governments, international organizations, and nongovernmental organizations, improve the institutional setting for the negotiation and implementation of new agreements and action programs, and strengthen the action capacity of the developing countries on these matters. The present paper points to and elaborates the need for a »World Environment and Development Organization« within the United Nations system, and outlines the shape it might be given. The intention here is to carry the debate, which has made considerable headway, into the science of politics and development. How will the expert community in the field of foreign relations and development cooperation, based on their theories and empirical knowledge, respond to the proposal?
Keywords: 300; Internationale Umweltpolitik; Umweltorganisation; Internationale Organisation; Welt